Muslim Entrepreneur Behavior in Kudus: Spirituality, Religiosity and Business - Mustaqim, Muhamad; Ghofur, Abdul; Sholihan, Sholihan (EQUILIBRIUM, 2022)
This paper aims to understand the behavioral tendencies of Muslim micro, small and medium entrepreneurs (MSMEs) in Kudus, on the dimensions of religion, spirituality and business activities. The research method used is field research with a qualitative approach, by conducting interviews and observations of the research object. Structured interviews were conducted with 17 informants, taking into account religion, business cluster and business location. The results of the study indicate that the tendency of business behavior of Muslim entrepreneurs is influenced by several factors, one of which is spiritual and religious factors. However, not all of this business behavior is motivated by spiritual and religious factors. Although, in general, economic factors are often the motivation for business behavior.